An investigation into the translation of hyperboles from vietnamese into english as manifested in english versions of truyện kiều (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
Being a stylistic device having a great power of expressive meaning, hyperbole is utilized wonderfully by Nguyễn Du to compose a lot of beautiful verses that contribute to make Truyện Kiều into a masterpiece. Arising from this, to render properly the hyperboles in Truyện Kiều from Vietnamese into English is very significant. This thesis is carried out to investigate hyperboles in Truyện Kiều on the aspect of translation equivalence. It will find out how they are transferred into English, the similarities and differences manifested in different English versions as well as the most effective and frequently-used procedures in the translation. As a consequence, the study will help the foreigners understand more clearly about hyperboles in Truyện Kiều; the teachers and learners of English manage better in rendering this fantastic stylistic device.